Green Marketing Appeal and Brand Image to Consumer Purchase Intention: A Study of the Body Shop in Medan City - Fahira, Tengku Nazwa; Siregar, Onan Marakali (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
The cosmetics industry worldwide has seen a remarkable expansion in tandem with a rise in consumer consciousness regarding environmental concerns and a desire for eco-friendly products. The Body Shop has emerged as a leading cosmetic brand owing to its dedication to sustainability and a compelling brand identity. This study seeks to investigate the impact of eco-friendly marketing and brand perception on consumer intent to purchase, both individually and collectively. The research methodology adopted is quantitative in nature, employing an associative approach. Information was gathered from a sample of 100 individuals who use products from The Body Shop in Medan City through purposive sampling. Statistical analysis was carried out using multiple linear regression with the aid of SPSS software. Findings shows that green marketing has a positive and significant effect on purchase intention (t-value = 5.214; sig. = 0.000 < 0.05; coefficient = 0.691). Conversely, brand image does not have a significant effect (coefficient = 0.114). Simultaneously, both variables significantly influence purchase intention with an adjusted R² value of 33%, while the remainder is influenced by other factors outside this research. These findings demonstrate the importance of green marketing strategies in shaping consumer purchasing decisions in the sustainable cosmetics sector.